ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR PADA MATA PELAJARAN BAHASA INDONESIA TAHUN AJARAN 2022/2023 - Agustin, Rizqi; Chamdani, Muhamad; Salimi, Moh. (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The study aimed to describe: the types of early reading difficulties to second grade students and (2) the factors affecting the early reading difficulties to second grade students. It was a qualitative case study. The objects were 27 second grade students at Jemur elementary school. Data collection techniques were interviews, observation, and document studies. Data analysis included data reduction, data presentation, and verification. The results indicated that (1) the types of early reading difficulties experienced by students in learning Indonesian were (a) reading words containing double vowels/diphthongs, (b) reading words containing multiple consonants/digraphs, (c) combining letters and syllables into words, and (d) disfluent reading; (2) Factors affecting early reading difficulties to second grade students at Jemur elementary school were internal factors such as interest and motivation and external factors such as learning process, facilities, and infrastructure, and family environment